Redistribuição da preciptação em seringueira - Rodrigues, Valdemir Antonio [UNESP] (My University, 2008)
The present work of research was developed in rubber tree plantation, clone RRIM 600, with 15 years of age, in the region of Jose Bonifácio - SP, situated 21°03′ latitude (s), 49°41′ of longitude (w) and 490 altitude of m, to the sum of the micro watershed of the river Barra Grande. The research had the purpose to evaluate the redistribution of precipitations in hidric year 1995/96, esteem the rain precipitation, effective, throughfall, stemflow and the interception by canopies of the rubber tree. They had been installed the open sky and under the canopy of the trees rain gauges and interception of trunk to quantify (mm) the redistribution of rains. The annual average rain precipitation was of 1053,6 mm, the throughfall of 699,4 mm and stemflow for the 92,3 mm. the interception by canopies and the precipitation effective had resulted in 261,9 and 791,7 mm; being these respectively 24.9% and 75.1% of the rain precipitation in the rubber tree.
Redistribution of the preciptation in rubber tree
Keywords: Interception by canopies; Rain precipitation; Rubber tree; Stemflow; Throughfall and effective; canopy; interception; precipitation (climatology); rainfall; stemflow; throughfall; Hevea brasiliensis